Padua prediction score may be inappropriate for VTE risk assessment in hospitalized patients with acute respiratory conditions: A Chinese single-center cohort study - Suqiao Yang; Yixiao Zhang; Xiaojing Jiao; Jiayu Liu; Wei Wang; Tuguang Kuang; Juanni Gong; Jifeng Li; Yuanhua Yang (International Journal of Cardiology: Heart & Vasculature, 2023)
Background: The Padua Prediction Score (PPS) recommended by the guidelines lacks effective external validation in a Chinese cohort. This study sought to assess the accuracy of the PPS to predict venous thromboembolism (VTE) risk in medical inpatients with acute respiratory conditions. Methods: This consecutive cohort study included 1,574 inpatients from January to August 2019. The occurrence rate of VTE in patients classified at high-risk and low-risk groups according to PPS and Caprini risk assessment model (RAM) was compared. The discriminatory capability of the RAMs was evaluated in all the patients and the subgroup without pharmacological prophylaxis. Reclassification parameters were also used to assess the clinical utility. Results: 170 (10.8%) patients were objectively confirmed as having VTE during hospitalization. The incidence rate of VTE in low-risk patients was 6.3% by PPS, which was significantly higher than that by Caprini RAM (2.6%, p < 0.001). The area under the curve (AUC) for PPS and Caprini RAM was 0.714 (95%CI, 0.672–0.756) and 0.760 (95%CI, 0.724–0.797), respectively (p = 0.003). The AUC of Caprini RAM was larger than PPS even in subgroups without pharmacological prophylaxis (0.774 vs 0.709, p = 0.002). Compared with Caprini RAM, the net reclassification index was estimated at 0.037 (p = 0.436), and integrated discrimination improvement was 0.015 (p = 0.495) by PPS. Conclusions: According to our cohort study, PPS may not be appropriate to predict VTE risk in hospitalized patients with acute respiratory conditions. An accurate, widely applicable, validated RAM needs to be further constructed in Chinese medical inpatients.